Review research as scientific inquiry - Kunisch, Sven; Denyer, David; Bartunek, Jean M.; Menz, Markus; Cardinal, Laura B. (Sage, 2022)
This article and the related Feature Topic at Organizational Research Methods were motivated by the concern that despite the bourgeoning number and diversity of review articles, there was a lack of guidance on how to produce rigorous and impactful literature reviews. In this article, we introduce review research as a class of research inquiries that uses prior research as data sources to develop knowledge contributions for academia, practice and policy. We first trace the evolution of review research both outside of and within management including the articles published in this Feature Topic, and provide a holistic definition of review research. Then, we argue that in the plurality of forms of review research, the alignment of purpose and methods is crucial for high-quality review research. To accomplish this, we discuss several review purposes and criteria for assessing review research's rigor and impact, and discuss how these and the review methods need to be aligned with its purpose. Our paper provides guidance for conducting or evaluating review research and helps establish review research as a credible and legitimate scientific endeavor.
Keywords: philosophy of science; epistemology; methods; meta-analysis; research synthesis; review articles; systematic literature reviews; integrative reviews; evidence-based management; rigor; impact; methodological fit